Urgensi Pendidikan Agama Islam Bagi Siswa Sekolah Dasar Dalam Membentuk Karakter - Rini Fitria; Arif Ramatullah (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2026)
This study aims to analyze the urgency of Islamic religious education in character building for elementary school students. The method used is qualitative with a literature study approach. The results of the study indicate that Islamic values ??such as honesty, responsibility, tolerance, and discipline can be instilled from an early age through Islamic Religious Education (PAI) learning. Religious education plays a strategic role as a moral foundation in facing the challenges of globalization and moral decadence. Contextual and enjoyable PAI learning in elementary schools greatly contributes to the formation of students' noble character. Islamic Religious Education that makes Islamic values ????instilled early in basic education will certainly make students have a very good character. At elementary school age, of course, teachers must choose very good learning methods, because at this age students still have a sense of play. Choosing methods that are adapted to the learning material certainly requires teachers to be able to hone their competencies so that the material can be accepted by students and applied in everyday life.